2001
DOI: 10.1182/blood.v98.10.2988
|View full text |Cite
|
Sign up to set email alerts
|

WASP and N-WASP in human platelets differ in sensitivity to protease calpain

Abstract: Mutations of Wiskott-Aldrich syndrome protein (WASP) underlie the severe thrombocytopenia and immunodeficiency of the Wiskott-Aldrich syndrome. WASP, a specific blood cell protein, and its close homologue, the broadly distributed N-WASP, function in dynamic actin polymerization processes. Here it is demonstrated that N-WASP is expressed along with WASP, albeit at low levels, in human blood cells. The presence of approximately 160 nmol/L rapidly acting N-WASP molecules may explain the normal capacity of WASP-ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
48
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 30 publications
5
48
0
Order By: Relevance
“…19 However, a more recent report suggested that platelets express very small amounts of N-WASP. 20 These observations are consistent with those of Hartwig et al 13 who had provided evidence earlier that, for platelets in suspension, Rac rather than Cdc42 is essential for actin polymerization. However, both Rac and Cdc42 are reportedly involved in the development of lamellipodia in spreading platelets.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…19 However, a more recent report suggested that platelets express very small amounts of N-WASP. 20 These observations are consistent with those of Hartwig et al 13 who had provided evidence earlier that, for platelets in suspension, Rac rather than Cdc42 is essential for actin polymerization. However, both Rac and Cdc42 are reportedly involved in the development of lamellipodia in spreading platelets.…”
supporting
confidence: 91%
“…Consistent with the idea, only WAVE2 was found at linear structures (including the rim area) in lamellipodia following permeabilization and fixation of spread platelets ( Figure 5B and data not shown). On the basis of reports that platelets do not express N-WASP or at best very small amounts, 19,20 and that platelets from patients with WAS lacking WASP appear to spread normally on the surface, 17,18,45 we postulate that WAVEs (especially WAVE2) and cortactin rather than WASP or N-WASP play the predominant role in the regulation of actin polymerization in the lamellipodia of platelets. Recently, it was reported that WAVE2 requires phosphatidylinositol 3,4,5-trisphosphate for localization and promotion of lamellipodia in cell lines.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…WASP in platelet lysates is degraded by the calcium-dependent protease calpain (16). We first determined whether WASP is a direct substrate for calpain.…”
Section: Wasp Is Unstable In the Absence Of Wipmentioning
confidence: 99%